β-Glucan reprograms alveolar macrophages via neutrophil/IFNγ axis in a murine model of lung injury - Renaud Prevel; Erwan Pernet; Kim A Tran; Abderrahmane Sadek; Mina Sadeghi; Elizabeth Lapshina; Leonardo F Jurado; Arnold S Kristof; Mohieddine Moumni; Jeremie Poschmann; Maziar Divangahi (eLife, 2025)
Alveolar macrophages (AMs) reside in the lower airways and play a crucial role in lung health and response to sterile inflammation and infections. AMs possess remarkable adaptability to different environmental challenges that can persist through their memory capacity (trained immunity). β-Glucan has been characterized as a potent inducer of central trained immunity by reprogramming haematopoietic stem cells in the bone marrow. In the present study, we show that systemic administration of β-glucan in mice induces peripheral trained immunity by reprogramming AMs in the lungs, in a Dectin1-independent manner. We furthermore demonstrate that AM reprogramming at both the transcriptional and metabolic levels exacerbate lung injury following bacterial (lipopolysaccharide) or viral (polyI:C) challenges via a neutrophil/IFN-γ-dependent manner. These findings identify an additional facet of β-glucan in trained immunity involving AM reprogramming and shed light on the potential detrimental effects of trained immunity.